The Role of Servant Leadership, Perceived Organizational Support (POS) on SMEs Performance through Organizational Citizenship Behavior (OCB) - Susanto, Agus (Journal of Industrial Engineering & Management Research, 2023)
This study aims to analyze the relationship between the variable Servant Leadership and Organizational Citizenship Behavior (OCB), analyze the relationship between Perceived Organizational Support (POS) and Organizational Citizenship Behavior (OCB), analyze the relationship between servant leadership and MSME performance, analyze the relationship between Perceived Organizational Support (POS) and MSME performance, and analyze the relationship between Organizational Citizenship Behavior (OCB) on MSME performance. This type of research is quantitative associative research, namely research that aims to determine the relationship between two or more variables. The respondents of this study were 278 SMEs leaders in Banten who were determined by simple random sampling method. Research data was obtained by distributing questionnaires online via social media. Each research indicator was measured using a Likert scale of 1-7 points scale and the degree of agreement from strongly agree to strongly disagree. The analytical tool used in this research is PLS (Partial Least Square) based SEM with SmartPLS 3.0 software data processing tool. The results of the hypothesis test show that the servant leadership variable has no significant effect on organizational citizenship behavior (OCB), Perceived organizational support (POS)) variable has a positive and significant effect on organizational citizenship behavior (OCB, The results of the hypothesis test show that the servant leadership variable has no significant effect on SMEs Performance, Perceived organizational support (POS) variable has a positive and significant effect on SMEs Performance,the organizational trust variable has not significant effect on MSME performance., organizational citizenship behavior (OCB has no significant effect on performance through organizational trust, organizational citizenship behavior (OCB ) does not mediate the relationship between Perceived organizational support (POS) and performance.Servant leadership has no significant effect on performance through Perceived organizational support (POS), organizational citizenship behavior (OCB) does not mediate the relationship between servant leadership on SMEs performance.